2018
DOI: 10.1080/10428194.2018.1459608
|View full text |Cite
|
Sign up to set email alerts
|

Variability of contribution of vitamin D receptor gene polymorphisms to outcome of HLA-matched sibling allogeneic bone marrow transplantation

Abstract: Graft-versus-host disease (GVHD) remains one of the major complications of hematopoietic stem cell transplantation (HSCT). Several etiological factors were investigated. Among these, vitamin D and hence its receptor (VDR) gene polymorphisms have gained much interest; however, the results are still controversial. Using PCR-RFLP, we genotyped VDR polymorphisms FokI (rs10735810), ApaI (rs7975232), and Taq1 (rs731236) in 80 patient/donor pairs according to DNA availability. No association was encountered between V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The association of VDR gene polymorphisms with major clinical outcomes following HSCT has been investigated in different studies with inconclusive results (116,143,(146)(147)(148)(149)(150). Therefore, further research in this field is warranted with larger study samples, including more recipients of different donor types (unrelated, haploidentical).…”
Section: Vdr As Biomarker In Hsctmentioning
confidence: 99%
“…The association of VDR gene polymorphisms with major clinical outcomes following HSCT has been investigated in different studies with inconclusive results (116,143,(146)(147)(148)(149)(150). Therefore, further research in this field is warranted with larger study samples, including more recipients of different donor types (unrelated, haploidentical).…”
Section: Vdr As Biomarker In Hsctmentioning
confidence: 99%
“…Interestingly, the results of these studies are quite variable. Some studies suggest roles for various polymorphisms in GVHD when present in the recipient only (8082), some studies suggest a role for VDR genotype in both the donor and recipient (83), while another more recent study found no significant association between GVHD and VDR polymorphisms in the donor nor recipient (84). Taken together, these results suggest that in some instances the a allele of VDR may play a role in aGVHD risk when present in recipients of HSCT.…”
Section: Effects Of Vitamin D On Gvhdmentioning
confidence: 99%
“…Taken together, these results suggest that in some instances the a allele of VDR may play a role in aGVHD risk when present in recipients of HSCT. However, not all studies have found such an association and the results may vary between different populations (84). One complicating factor of these studies was that the vitamin D status of the individuals studied was often unknown.…”
Section: Effects Of Vitamin D On Gvhdmentioning
confidence: 99%